Simulations of Polarimetric, X-Band Radar Signatures in Supercells. Part II: ZDR Columns and Rings and KDP Columns - Snyder, Jeffrey C.; Bluestein, Howard B.; Dawson II, Daniel T.; Jung, Youngsun (Journal of applied meteorology and climatology, 2017)
A high-resolution numerical model and polarimetric forward operator allow one to examine simulated convective storms from the perspective of observable polarimetric radar quantities, enabling a better comparison of modeled and observed deep moist convection. Part I of this two-part study described the model and forward operator used for all simulations and examined the structure and evolution of rings of reduced copolar cross-correlation coefficient (i.e., ρ hv rings). The microphysical structure of upward extensions of enhanced differential reflectivity ( Z DR columns and Z DR rings) and enhanced specific differential phase ( K DP columns) near and within the updrafts of convective storms serve as the focus of this paper. In general, simulated Z DR columns are located immediately west of the midlevel updraft maximum and are associated with rainwater lofted above the 0°C level and wet hail/graupel, whereas Z DR rings are associated with wet hail located near and immediately east of the midlevel updraft maximum. The deepest areas of Z DR > 1 dB aloft are associated with supercells in the highest shear environments and those that have the most intense updrafts; the upper extent of the Z DR signatures is found to be positively correlated with the amount and mean-mass diameter of large hail aloft likely as a by-product of the shared correlations with updraft intensity and wind shear. Large quantities of rain compose the K DP columns, with the size and intensity of the updrafts directly proportional to the size and depth of the K DP columns.